APPLICABILITY MAGNITUDE OF CLINICAL PRACTICE GUIDELINES FOR DIAGNOSIS, PREVENTION AND TREATMENT OF OSTEOPOROSIS AMONG FAMILY PHYSICIANS: A CROSS SECTIONAL STUDY - Sheikh Abdul Khaliq; Syed Baqir Shyum Naqvi; Syed Muhammad Mubeen et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: Clinical Practice Guidelines are developed by professional groups. Guideline development process should be strategically rigor and methodologically appropriate; otherwise, resulting recommendations will not be implemented successfully. Variability in guidelines quality and deviations from basic standards are possible. Main aim of study is to evaluate the magnitude of applicability of International Osteoporosis Foundation Guidelines for diagnosis, prevention and treatment of Osteoporosis in Asia for Pakistani population by family physicians.SUBJECTS AND METHODS: Cross sectional study was conducted during December 2014 to January 2017. Data has been collected from 50 family physicians practicing in Karachi. Sample size was determined by power analysis technique. Six main domains provided by AGREE – II instrument were evaluated; scope and purpose, stakeholder involvement, rigour of development, clarity of presentation, applicability and editorial independence in addition to overall quality of guideline. Data was analyzed through SPSS 23 using descriptive statistics. RESULTS: Among 50 family physicians, practitioners from private hospital are 10 (20%),private clinics are 40 (80%). Magnitudes of six domains were 66% scope and purpose, 65% stakeholder involvement, 84% rigour of development, 86% clarity of presentation, 84% applicability and 61% editorial independence, all these domains are signiﬁcantly (p<0.003) lower compares to ideal score. CONCLUSION: Examination of the overall assessment of guideline revealed that majority of family physicians did not reject the guideline.